Association between TLR1 polymorphisms and alopecia areata. (September 2014) - Seok, Hosik; Suh, Dong Woo; Jo, Byungchul; Lee, Hwang-Bin; Jang, Hyang Mi; Park, Hun Kuk; Lew, Bark-Lynn; Chung, Joo-Ho; Sim, Woo-Young
Abstract Toll-like receptors (TLRs) may contribute to the process of autoimmune attacks on hair follicles. To investigate whether the TLR1 gene polymorphisms are associated with the development and clinical features of alopecia areata (AA), a case-control comparison of two single nucleotide polymorphisms (SNPs) (rs4833095, Asn248Ser and rs5743557, −414C > T) of TLR1 were studied in 239 AA patients and 248 controls. Using multiple logistic regression model, odds ratios, 95% confidence intervals and corresponding p values were estimated. Clinical features were analyzed based on the age of onset, family history, type of AA, nail involvement and body hair involvement. The missense SNP rs4833095 was significantly associated with the development of AA (codominant2, p = 0.002; recessive, p = 0.001; log-additive, p = 0.0071; and allele frequency, p = 0.0066). The promoter SNP rs5743557 was weakly associated with the development of AA (codominant2, p = 0.019; recessive, p = 0.032; log-additive, p = 0.020; and allele frequency, p = 0.03). In the clinical features, rs4833095 was only weakly associated with age of onset between 15 and 50 years (codominant2, p = 0.043 and recessive, p = 0.022). The results suggest that rs4833095 of TLR1 may be associated with the susceptibility for AA in the Korean population.